Correlation Between C-Reactive Protein (CRP) and Lactate Dehydrogenase (LDH) Levels with Severity and Predicting Outcome of Confirmed Covid-19 at Arifin Achmad Hospital, Riau Province (Nusantara Science and Technology Proceedings, 2022)
Coronavirus Disease 19 (COVID-19) triggers a series of inflammatory processes. The inflammatory process damages the hematopoiesis system, especially the bone marrow, releasing white blood cells and stimulating the liver to secrete acute phase proteins such as ferritin, C-Reactive Protein (CRP), and Lactate Dehydrogenase (LDH). Laboratory tests including CRP and LDH can determine the severity of COVID-19. This study has the purpose to investigate the correlation between LDH and CRP with the severity of confirmed COVID-19 patients and predicting the outcome. This study used a cross-sectional design to determine whether CRP and LDH were able to predict mortality in confirmed COVID-19 patients about illness severity who were hospitalized from April 2020 - July 2021 at Arifin Achmad Hospital Pekanbaru. This study included 522 patients, of which 73 patients (14.00%) died and 449 patients (86.00%) experienced improvement during treatment. The mean LDH and CRP levels in this study were 293.47 ± 192.64 u/L and 55.48 ± 79.03 u/L, respectively. The area under the curve (AUC) ROC for patient outcomes on LDH and CRP examinations was 0.74 and 0.80 with cut-off levels of LDH and CRP to predict mortality in COVID-19 patients of 297 (sensitivity, specificity, PPV, NPV = 60.2%, 53.9%, 17.5%, and 89.3%) and 52 (sensitivity, specificity, PPV, NPV= 63.0%, 78.1%, respectively, 31.9%, and 92.8%) with p-values for all results <0.001. CRP and LDH testing can be used to predict death, but in this study, CRP has an advantage in predicting death.